Analysis of Social Media Influencers on Purchase Intention through Perceived Value as a Mediating Variable - Hanifah, Bunga; Ramdan, Asep Muhamad; Jhoansyah, Dicky (Dinasti Publisher, 2024)
Lazada, one of the largest e-commerce in Southeast Asia, experienced a decrease in the number of visitors in early 2023. This study aims to analyze the influence of social media influencers on purchase intention through perceived value as a mediating variable for Lazada users in Sukabumi City. The research method used is quantitative with a sample size of 180 respondents. Data analysis techniques using Structural Equation Modeling Partial Least Square (SEM-PLS). The results showed that social media influencers have a positive and significant effect on perceived value. Social media influencers have no significant effect on purchase intention. Perceived value has a positive and significant effect on purchase intention. Perceived value is not effective in mediating the relationship between social media influencers and purchase intention, because the direct effect is greater than the indirect effect. In conclusion, Lazada needs to increase the role of social media influencers and perceived value to encourage user purchase intention, but it needs a more effective strategy in integrating these two factors.